2023
DOI: 10.14712/fb2023069020059
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Short Leukocyte Telomeres and Oxidative Stress with the Presence and Severity of Lung Cancer Explored by Principal Component Analysis

Milica Belić,
Miron Sopić,
Marina Roksandić-Milenković
et al.

Abstract: Lung cancer (LC) is the second most common malignancy and leading cause of cancer death. The potential “culprit” for local and systemic telomere shortening in LC patients is oxidative stress. We investigated the correlation between the peripheral blood leukocyte (PBL) telomere length (TL) and the presence/severity of LC and oxidative stress, and its usefulness as LC diagnostic marker. PBL TL was measured in 89 LC patients and 83 healthy subjects using the modified Cawthon RTq-PCR method. The relative PBL TL, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…It was demonstrated that both short and long telomere lengths have been associated with a high risk of cancer incidence. In particular, the majority of retrospective studies report an increased risk of cancer in individuals carrying shorter telomeres in blood leukocytes [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ] but, in our knowledge, the role of shortened telomere length in MPT development has not yet been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that both short and long telomere lengths have been associated with a high risk of cancer incidence. In particular, the majority of retrospective studies report an increased risk of cancer in individuals carrying shorter telomeres in blood leukocytes [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ] but, in our knowledge, the role of shortened telomere length in MPT development has not yet been demonstrated.…”
Section: Introductionmentioning
confidence: 99%